(untitled) (Gaceta Técnica, 2026)
This research aims to propose urban guidelines for the planning of public spaces in Barquisimeto, Lara State, Venezuela, aligned with global sustainable development trends. A mixed-methods approach was employed, integrating documentary and analytical research with field-based study. The process involved a multi-scale assessment of public spaces and current regulatory frameworks, benchmarked against successful international examples. The Central Macrosector was selected as the study area, identifying the Cultural Heritage Promenade" as a vital axis for the city. The proposal is grounded in four strategic pillars: sustainability, accessibility, sense of ownership, and comfort. The results provide an operational roadmap that goes beyond mere aesthetics, seeking to transform Barquisimeto into a benchmark for innovative and successful urban management regarding public space